2018
DOI: 10.1038/s41598-018-29584-3
|View full text |Cite
|
Sign up to set email alerts
|

Nature and nurture effects on the spatiality of the mental time line

Abstract: The nature-nurture debate regarding the origin of mental lines is fundamental for cognitive neuroscience. We examined natural-nurture effects on the mental time line, applying three different challenges to the directionality of time representation. We tested (1) patients with left-neglect and healthy participants, who are (2) left-to-right or right-to-left readers/writers, using (3) a lateralized left-right button press or a vocal mode in response to a mental time task, which asks participants to judge whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…The ANOVA on RTs revealed a significant main effect of Group [F (2,27) = 3.83, P = 0.034, η 2 p = 0.22] indicating generally slower RTs in vmPFC (1201 ms) and control patients (1243 ms) compared to healthy controls (853 ms). The main effect of Self-projection [F (2,54) = 6.32, P = 0.003, η 2 p = 0.19] was significant, such that all participants were slower at recognizing events while projected to the past (1074 ms) and to the future (1075 ms) than to the present (925 ms, both P = 0.003) ( Figure 3B ), replicating previous findings ( Arzy et al , 2008 ; Anelli et al , 2018 ). The interaction Event × Self-projection was also significant [F (2,54) = 4.31, P = 0.02, η 2 p = 0.14], such that in the past self-projection condition (1159 vs 990 ms, P = 0.003), but not in the other conditions ( P > 0.64 in both cases), participants were faster at recognizing personal compared to non-personal events, reflecting, again, better memory for the personal compared to the non-personal (remote) past.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The ANOVA on RTs revealed a significant main effect of Group [F (2,27) = 3.83, P = 0.034, η 2 p = 0.22] indicating generally slower RTs in vmPFC (1201 ms) and control patients (1243 ms) compared to healthy controls (853 ms). The main effect of Self-projection [F (2,54) = 6.32, P = 0.003, η 2 p = 0.19] was significant, such that all participants were slower at recognizing events while projected to the past (1074 ms) and to the future (1075 ms) than to the present (925 ms, both P = 0.003) ( Figure 3B ), replicating previous findings ( Arzy et al , 2008 ; Anelli et al , 2018 ). The interaction Event × Self-projection was also significant [F (2,54) = 4.31, P = 0.02, η 2 p = 0.14], such that in the past self-projection condition (1159 vs 990 ms, P = 0.003), but not in the other conditions ( P > 0.64 in both cases), participants were faster at recognizing personal compared to non-personal events, reflecting, again, better memory for the personal compared to the non-personal (remote) past.…”
Section: Resultssupporting
confidence: 85%
“…Healthy as well as brain-damaged controls showed a comparable performance in recognizing relative-future and relative-past events, hence the selective deficit evinced by vmPFC patients with relative-future events is unlikely to merely reflect task difficulty. Note, also, that vmPFC patients’ false recognition of future events also emerged in the past self-location condition, that is, when dealing with events that were not actually future (with respect to the present time), and therefore it does not simply denote a problem in distinguishing familiar from novel events, or factual from potential, hypothetical events (see also Anelli et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, participants responded faster to future events compared to past events, perhaps reflecting a future-oriented thinking mechanism (Arzy et al, 2008(Arzy et al, , 2009. Interestingly, this effect is reversed in older adults, and may also be manipulated by deviations in spatial attention and writing direction (Anelli, Ciaramelli, Arzy, & Frassinetti, 2016b;Anelli et al, 2018). Future studies may investigate whether self-reference in the person domain as found here is sensitive to such manipulations as well.…”
Section: Discussionmentioning
confidence: 69%
“…In view of the metaphor theory, time and space domains are independent at the beginning of development and become linked, asymmetrically, depending on individual experience, language, and culture (for a critical comparison of the two theories, see Winter et al, 2015). In support of the metaphor theory, there is evidence that people from different cultures and writing languages lay out time in space differently (Tversky et al, 1991; Fuhrman and Boroditsky, 2010; Anelli et al, 2018). For example, Tversky et al (1991) asked participants to map events on a ruled-off square sheets of paper.…”
Section: Introductionmentioning
confidence: 94%